INTEREST OF STUDENT FEBI IAIN FATTAHUL MULUK PAPUA STUDENT INTEREST IN SAVING IN SHARIAH BANK - M. Rusulin Risgin; Ahmad Baghis Haidar; Shimah Fauziah Yeubun; Fachrudin Fiqri Affandy (Institut Agama Islam Negeri Lhokseumawe, 2023)
This study aims to examine and analyze the interest in saving in FEBI IAIN Fattahul Muluk Papuan students in Islamic banks. Islamic campus students tend to use services or services from Islamic banks, this is due to the level of Islamic financial literacy that has grown during their studies and is followed by adequate Islamic financial inclusion found in the campus environment. Papua province in 2022 Islamic financial literacy is 45.19% followed by Islamic financial inclusion of 76.36%. It is recorded that in 2022 students who have accounts at Islamic banks account for 90% of the total students as a whole however, there is a decrease every year, moreover there are problems with the customer data security system. This study used a quantitative method with an explanatory research approach and was analyzed using SmartPls version 3. The study population was all FEBI students by distributing questionnaires to 75 respondents who already had accounts at Islamic banks. The results of the study show that there are 2 important variables that can explain the factors of student interest in saving at Islamic banks, including Islamic financial literacy and Islamic financial literacy. These two variables have a positive and significant effect on students' interest in saving at Islamic banks. This study recommends that all parties, both government agencies and campuses, continue to educate the public about sharia financial products and shariah financial management, especially in the millennial generation, to further increase Islamic financial inclusion so that all parties are capable of accessing finance.